International education: a tertiary level industry update - Naidoo, Vik (Sage Publications, 2006)
Recent developments in the international education industry are notable in three respects. First, international student mobility has more than doubled in the last two decades or so. Second, programme mobility encompassing distance education has also led to new forms of cross-border education. Third, institution mobility through such commercial deals as franchises and twinning arrangements are becoming an increasingly important feature of cross-border education, although on a limited scale. Such developments are leading to the emergence of a new market place for the international education industry. This article documents and analyses trends in painting a picture of these contemporary developments in cross-border education.